Closing session: Putting Jack Mezirow’s Ideas into Context - Michael Newman (Adult Education Research Conference, 2015)
The author argues that all adult education theory is either humanist or socialist. He reviews some of Jack Mezirow’s ideas with this idea in mind.
Keywords: humanism; socialism